Potential Effect of Orthosiphon aristatus Leaf Extract in Improving Collagen 1 Alpha 1 Expression in Hyperglycemia-Induced Rats - Aisyah, Riandini; Risanti, Erika Diana; Jatmiko, Safari Wahyu; Asfarina, Fatin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Diabetes mellitus involves many mechanisms, the collagen metabolism pathway with very complex interactions and its regulation can contribute to the development of diabetes complications. The collagen 1 alpha 1 (COL1A1) gene plays an important role in the diabetes melitus pathway in adipose tissue by regulating adipocyte function, insulin resistance, and glucose metabolism. COL1A1 expression is positively correlated with insulin resistance and negatively correlated with insulin sensitivity and is identified as a potential therapeutic target for type 2 diabetes. The cat's whisker plant (Ortosiphon aristatus) pharmacologically has hypoglycemic activity and increases insulin expression. This study aims to observe the potential of cat whisker leaf extract (Ortosiphon aristatus) in increasing the expression of the COL1A1 gene and is protective against increased blood sugar levels in hyperglycemia-induced Rattus norvegicus. The experimental design with pretest and posttest controlled group design was carried out by dividing 18 test animals into six groups of non-diabetic negative control, diabetic negative control, metformin as positive control, doses of 100, 200, and 400 mg/kgBW. Induction of hyperglycemia with streptozotocin 65 mg/kgBW and nicotinamide 230 mg/kgBW peritoneal injection. The extract treatment is given for 14 days. Blood sugar level measurements were carried out at the treatment’s beginning and end. Adipose tissue was taken to examine COL1A1 gene expression by real time PCR technique by calculating the ratio of the cycle of tresh-hold COL1A1 to the internal ?-actin gene. The results of Kruskall Wallis test showed no significant difference in COL1A1 gene expression between groups and the Spearmen correlation test showed no relationship between blood sugar levels and COL1A1 gene expression (p>0.05). There was a decrease in blood sugar levels before and after treatment for all treatment groups.